Beyond the midpoint: achieving the millennium development goals - United Nations Development Programme (UNDP) (2010)
That document enshrined the Millennium Development Goals as the international community’s collective commitment to create a better tomorrow for billions of people, prioritizing efforts to reduce poverty and hunger; empower women; increase access to essential services like education, healthcare, clean water, and sanitation; and forge strong global partnerships for development. It is in all our interests that these goals are met. We cannot achieve a more equitable and sustainable world when one billion people are hungry, or when their lives are endangered by easily preventable health risks; when a lack of education limits the poor’s potential, or stifles innovation; when women are not able to participate as equal members in society; and when our natural resources become depleted and degraded. There are encouraging signs that our world is moving in the right direction towards a number of the MDGs. Eighty eight per cent of children in the developing world as a whole were enrolled in primary school in 2007, up from 83 per cent in 2000.